Performance of a reactive magnetron sputtering ion source using water vapor plasma. Issue 1 (1st April 2022) - Catapang, Allen Vincent; James Edward Hernandez, II; Vasquez, Magdaleno R.; Wada, Motoi
Abstract: One of the methods used to produce ions of metals and metal oxides is through extracting them from a magnetron sputter-type ion source. Metal nanoparticles, such as zinc oxide (ZnO), can be deposited using this method. However, low-energy conditions are required to prevent damage to the substrate. The extraction of ions from a differentially pumped, reactive magnetron sputtering source with a pulsed, conduit-type extraction electrode is investigated, with Zn as the metal target and argon and water vapor as discharge support and reactive gases, respectively. The use of water vapor has been shown to improve the properties of ZnO, through hydrogen doping. Using a quadrupole mass analyzer, the species produced from the ion source were detected and identified. Ar, H2 O, H3 O, and Zn ions were extracted using the pulsed extraction electrode, and the intensity of the extracted ions were found to be frequency dependent. Extraction of ions were observed starting from-40 V extraction potential using a Faraday cup, and the ion beam current appeared to increase in proportion to the extraction voltage. A mechanism for realizing ion extraction using an alternating extraction potential is proposed.